1993
DOI: 10.1113/jphysiol.1993.sp019922
|View full text |Cite
|
Sign up to set email alerts
|

Selective brain cooling in goats: effects of exercise and dehydration.

Abstract: SUMMARY1. Measurements of brain and central blood temperature (Tbr and Tbl), metabolic rate (MR) and respiratory evaporative heat loss (REHL) were made in trained goats walking on a treadmill at 4'8 km h-' at treadmill inclines of 0, 5, 10, 15 and 20 % when they were fully hydrated and at 0 % when they had been deprived of water for 72 h.2. In hydrated goats, exercise MR increased progressively with increasing treadmill incline. Both Tbl and Tbr rose during exercise, but Tbl always rose more than Tbr, and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
13
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
5
13
0
Order By: Relevance
“…Both species apparently used panting and sweating as a mechanism for cooling, and S used panting as the main evaporative cooling system, which is consistent with the general pattern for this species (Silanikove, 2000b). On the other hand, G used sweating as the main evaporative cooling system (Dmi'el, 1986;Baker and Nijland, 1993). Reduced sweating during dehydration and/or excessive heat storage resulted in increased body temperature and selective brain cooling (Dmi'el, 1986;Bakernd and Mijland, 1993), which most likely relates to the thermolability observed in G from the present experiment.…”
Section: Discussionsupporting
confidence: 76%
“…Both species apparently used panting and sweating as a mechanism for cooling, and S used panting as the main evaporative cooling system, which is consistent with the general pattern for this species (Silanikove, 2000b). On the other hand, G used sweating as the main evaporative cooling system (Dmi'el, 1986;Baker and Nijland, 1993). Reduced sweating during dehydration and/or excessive heat storage resulted in increased body temperature and selective brain cooling (Dmi'el, 1986;Bakernd and Mijland, 1993), which most likely relates to the thermolability observed in G from the present experiment.…”
Section: Discussionsupporting
confidence: 76%
“…Nijland and Baker (35) reported that although hypohydration (BW was reduced by 8.6%, and P osm was increased by 21 mosmol/kgH 2 O) reportedly shifts the core temperature threshold for an increase in sweating upward in exercising goats, as has been seen in exercising humans (17,44), hypohydration does not change the slope of the regression line relating blood temperature (at right atrium) to respiratory evaporative water loss (E res , index of panting response). Moreover, Baker and Nijland (6) reported that although the regression line relating blood temperature (at right atrium) to E res was shifted downward by hypohydration (BW was reduced by 9.2%) in the exercising goat, the shift was small. We therefore suggest that in goats (and humans), which show increases in both sweating and ventilation with increases in core temperature, hypohydration has little effect on the ventilatory response to an increase in core temperature during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, for example, that hypohydration attenuates the ventilatory response to an increase in core temperature in exercising dogs (3), resting fowl (2), resting cats (5,12,13), and resting rabbits (46). On the other hand, hypohydration reportedly leads to an increase in ventilation in resting rabbits (7) but little or no change in ventilation in exercising goats (6,35). Thus the effect of hypohydration on the ventilatory response to an increase in core temperature is still not completely understood in animals and could differ among species.…”
mentioning
confidence: 99%
“…But the concept was applied more generally to euhydrated mammals when Taylor showed an increase in the evening rectal temperature of several euhydrated ungulate species when they were exposed to diurnal heat load in a climate chamber (Taylor, 1970). The original camel data could have been partly explained as dehydration-induced hyperthermia, wherein evaporative heat loss is stimulated only at a higher threshold T c (Baker and Nijland, 1993;Doris and Baker, 1981;Taylor, 1970). But the camels also exhibited a lower than normal T c in the morning, which cannot be explained as an effect of dehydration inhibiting the evaporative response to heat load.…”
Section: Introductionmentioning
confidence: 99%